PENGARUH PERKEMBANGAN VOLUME PENJUALAN TERHADAP PENDAPATAN ANEKA KERAJINAN ROTAN PADA PERUSAHAAN UD.MAMASE DI DESA SULI - Marlen Laipiopa; Merryl Pelamonia; Stevie Sahusilawane (P3M Politeknik Negeri Ambon, 2022)
Marketing is part of company management and is also an important factor. Marketing is usually a way or strategy by a company or producer to attract customers or consumers. It is important for the company to know the position of the product being sold because the more consumers who want the product, it will automatically affect the increase in sales volume. For this reason, the aim is to determine the effect of sales volume on revenue. What is tested in this study is sales volume as the independent variable and income as the dependent variable. The population in this study are consumers of the company UD. Mamase RT 047 Suli Village. The sample of this study amounted to 50 people. The sampling technique used was non-probability sampling with incidental sampling approach. The analytical tool used is simple linear regression analysis at a significance level of 5%. The results of this study prove that it can be said that sales volume has a positive and significant effect on income at the company UD. Mamase RT 047 Suli Village.Keywords: Sales Volume, Revenue